Linguistic Features Acquired by a Language of A Speaking Society - Althory, Abdallah Ali Ali (Journal of Arabic Language Sciences and Literature, 2022)
This paper aimed at investigate an important linguistic issue related to the features of the human language that is acquired from the speaking society. There are subjective linguistic features and acquired linguistic features by the speaking society. The writing linguistic feature as termed by language speakers is the most common acquired linguistic feature, and the feature of verbal inflection that increases the capacity and richness of the language, the structural feature based on the linguistic rules set by the linguists of a language, the feature of influence and vulnerability, the feature of receptiveness to inflectional and derivational morphology, and the feature of renewability, scalability and development at all linguistic levels, phonetic, syntactic and semantic.In order to achieve the objective of this study, the researcher used the descriptive and inductive method through investigating the elements and considered references related to the nature of the study topic.The results of the study revealed that there are linguistic features acquired from a speaking society and also there are features of that society, which should have the appropriate ability to comprehend its language according to its fundamentals and rules. The results also found and added new features. Hence, the results found that there is an evident and accurate association between the language and the speaking society. In light of the findings, the study recommended to conduct in-depth investigation for the linguistic features of the language acquired from the society, as they are more relevant to the truth, and they are the features resulting from the linguistic use by the speaking society of that language, and due to its importance in describing any language in an accurate manner.
Keywords: linguistic features; language; society